Oferta de sódio na alimentação em creches municipais: um risco à saúde - Anabelle Retondario; Débora Letícia Frizzi Silva; Márcia Aurelina de Oliveira Alves; Cláudia Choma Bettega Almeida; Suely Teresinha Schmidt; Sila Mary Rodrigues Ferreira (O Mundo da Saúde)
This paper aimed to determine sodium amount in meals offered to children from 12 to 36 months old, in municipal child daycare centers, using laboratorial analysis. The study was conducted in 4 child daycare centers from a city in the metro- politan region of Curitiba/PR, Brazil, randomly selected after complex sampling techniques. From June to November/2013, samples of the 6 daily meals served to children were collected in 4 child daycare centers, for 5 non-consecutive days, total- ing 20 days and 120 samples analyzed. Sodium content was determined by the method of chlorides by volumetry and the results were compared to 4 parameters, as follows: 1) maximum sodium value recommended by PNAE to full-time school feeding, 2) tolerable upper intake level (UL) for the age group, 3) compliance to maximum 70% of tolerable upper intake level (UL) for the age group, and 4) maximum sodium value recommended by PNAE to a single meal. The average amount of sodium offered to children was 1251mg/day, which met PNAE’s guidelines and corresponded to 83.4% of UL for age. As to sodium content in a single meal, 100% of lunches and 60% of dinners exceeded the maximum recommended by PNAE, indicating risk factor to hypertension in childhood and highlighting intervention required in this population.